Pro ASP.NET for SQL Server: High Performance Data Access for Web Developers - Stehling, Brennan (Apress, 2012)
This book covers the middle ground between ASP.NET and SQL Server that is not covered sufficiently by books that focus on these two big pieces independently. I wrote this book to focus on the bridge between these two systems to reveal all of the techniques and features available to developers so that you could learn to fully leverage these two technologies, which were designed very cleverly to work together. As you read the book and work through the sample projects, my hope is that you will discover features that you did not know about previously that will help you make your websites faster and easier to maintain.